2012
DOI: 10.1371/journal.pone.0051976
|View full text |Cite|
|
Sign up to set email alerts
|

Development of Models for Predicting the Predominant Taste and Odor Compounds in Taihu Lake, China

Abstract: Taste and odor (T&O) problems, which have adversely affected the quality of water supplied to millions of residents, have repeatedly occurred in Taihu Lake (e.g., a serious odor accident occurred in 2007). Because these accidents are difficult for water resource managers to forecast in a timely manner, there is an urgent need to develop optimum models to predict these T&O problems. For this purpose, various biotic and abiotic environmental parameters were monitored monthly for one year at 30 sites across Taihu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…In this study, regression analysis demonstrated that T&O compounds were highly correlated with certain water quality parameters (e.g., TN, pH and S 2− ) in groups M and H, which exhibited black bloom. These strong relationships are also supported by several previous studies (Downing et al, 2010;Qi et al, 2012). In addition, the absolute value of r 2 was generally higher in group H than in group M. These results indirectly suggest that T&O compounds are strongly correlated with black bloom.…”
Section: Dynamics Of Taste and Odor Compounds In Black Bloomsupporting
confidence: 87%
“…In this study, regression analysis demonstrated that T&O compounds were highly correlated with certain water quality parameters (e.g., TN, pH and S 2− ) in groups M and H, which exhibited black bloom. These strong relationships are also supported by several previous studies (Downing et al, 2010;Qi et al, 2012). In addition, the absolute value of r 2 was generally higher in group H than in group M. These results indirectly suggest that T&O compounds are strongly correlated with black bloom.…”
Section: Dynamics Of Taste and Odor Compounds In Black Bloomsupporting
confidence: 87%
“…In September, the decline of temperature appeared to trigger a cell death and/or sinking process in the dense Microcystis population, causing a continual decrease in cell density (Qi et al . ). Under this condition, types 6, 9 and 10 arose in the Microcystis population rapidly, replacing type 1 and other summer strains.…”
Section: Discussionmentioning
confidence: 97%
“…During this time, the Hanjiang River flows fast and turbid, and the range of measured discharge was 800 to 8000 m 3 s −1 in 2010 (Yang et al 2012). In Gonghu Bay (Lake Taihu), the average Secchi depth was 117 cm in the spring of 2010 (Qi et al 2012). Diatoms were isolated according to standard phycological methods (Stein and Hellebust 1979).…”
Section: Methodsmentioning
confidence: 99%
“…meneghiniana is often a dominant species in relatively calm water conditions (Qi et al 2012;Zeng et al 2007) and is considered as a large niche breadth species (Wang et al 2010). S. parvus is found in many temperate lakes at low to modest relative abundance (Sokal 2007).…”
Section: −1mentioning
confidence: 99%